Understanding Patient Revisit Intention and Word of Mouth in Healthcare Services: A SERVQUAL-Based Framework with Higher-Order Constructs - Clarissa Frances Mandita Putri; Vonny Widya Sudirman; Jovita Irawati (Jurnal Manajemen dan Kewirausahaan, 2025)
Healthcare quality plays a crucial role, but improving access to healthcare must be prioritized alongside population growth to ensure equitable and sustainable accessibility. This study investigates the impact of hospital service quality on perceived value and patient satisfaction. Additionally, perceived value affects satisfaction, revisit intention, and word of mouth, while patient satisfaction impacts revisit intention and word of mouth. This study employs a quantitative method using an online survey of 174 respondents across five cities in Indonesia. The research data were analyzed using multivariate statistics, specifically variance-based structural equation modeling. The outcomes of the analysis indicate that all the hypotheses proposed are statistically supported. Service quality in hospitals positively and significantly affects perceived value and satisfaction. Furthermore, perceived value affects satisfaction, revisit intention, and word of mouth. Satisfaction also significantly affects revisit intention and word of mouth. This study develops a service quality framework within the literature on hospital service quality and measurement using Higher-Order Constructs. Hospitals can enhance patients' perceived value and foster sustainable satisfaction by focusing on the service quality framework. This strategy is crucial in addressing competition in the healthcare market, particularly in attracting and retaining patients amid the ongoing dynamics of healthcare system reforms.